Schizophrenic active neutrinos and exotic sterile neutrinos - Machado, A. C. B. [UNESP]; Pleitez, V. [UNESP] (Elsevier B.V., 2011)
We implement a schizophrenic scenario for the active neutrinos in a model in which there are also exotic right-handed neutrinos making a model with a local U(1)(B-L) anomaly free. Two of right-handed neutrinos carry B - L = -4 while the third one carries B - L = 5. Unlike the non-exotic version of the model, in which all right-handed neutrinos carry the same B - L = -1 charge, in this case the neutrinos have their own scalar sector and no hierarchy in the Yukawa coupling in the Dirac mass term is necessary. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Neutrinos; B - L symmetry; Quark and lepton masses and mixing